D. G. Rossetti’s Trip to Paris and Belgium: A Journey Between Past and Present - Raphaël Rigal (Cahiers Victoriens et Edouardiens)
In 1849, Dante Gabriel Rossetti and William Holman Hunt undertook a trip to France and Belgium, with the specific goal of visiting art collections in Paris, Brussels, Bruges, Antwerp and Ghent. Despite not being as exotic as the expeditions of Richard Burton or David Livingstone, this trip was particularly meaningful, not only because of the context (the early years of the Pre-Raphaelite Brotherhood, soon after the 1848 Revolutions) but also because it was related by Rossetti himself, who wrote a series of poems during the journey and sent them in letters to his brother William Michael and some other members of the Brotherhood. These poems, collectively gathered under the title ‘A Trip to Paris and Belgium’, focus on different aspects of the trip: some of them describe the journey itself, by boat, train, or coach, from London to Antwerp and back; some of them describe places and events, for instance their arrival and connection in Paris; some others let transpire historical and political commentary under a sheen of ekphrasis. Overall, there is in the collection a more formal contrast between travel poems properly speaking, that is to say the texts describing the journey, and what I would call ‘static poems’, that is to say the texts written in the places visited. This paper will focus on the potential political role of these poems, established through this contrast: the elaboration of a Pre-Raphaelite realm of memory through Rossetti’s and Hunt’s contact with modernity. This contact is transcribed through a hybridisation of words and images which builds on the Pre-Raphaelite program and crystallises the two artists’ experience to transmit it to Pre-Raphaelite brothers waiting for them in Britain.